Sistem Informasi Alumni (Tracer Study) Berbasis Web Pada SMA Negeri 2 Bungo - Mashuri, Mashuri; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2023)
The tracer study activity is one of the activities that has a very strategic value in school development. Tracer study serves to determine the potential of graduates in the community, evaluation facilities in the development of learning process facilities and infrastructure in the future, improve the quality of graduates who are able to master science and technology, and achieve graduates with qualifications that are in accordance with the needs of the labor market so that they can be absorbed by the workforce. maximum. The purpose of this research is to analyze, design and make prototypes related to tracer studies at SMA Negeri 2 Bungo. This research produces a prototype tracer study design for SMA Negeri 2 which contains information about alumni data, information, documents, reports, several other menus. In addition, this study also uses object-based system analysis modeling, namely Use Case Diagrams, Class Diagrams and Activity Diagrams.